Military Capability Sustenance: Providing Effective Supports Through Lifespan - (Retired), Lt Kol Hamzan bin Abd Jamil; Nair, Lt Kol Mahendar a/l Sekaran; Murr, Lt Kol Ass Prof Ir. Dr. Muhamad bin; Ismail, Ass Prof Dr. Mohd Nazri bin (International Journal of Engineering and Technology, 2018)
The focus of this paper is to evaluate the implementation of Integrated Logistics Support (ILS) in the Malaysian Armed Forces (MAF). ILS is a disciplined and structured analysis approach, encompasses of management and technical activities, aimed to identify and improve supportability to achieve reliability and availability at optimising life-cycle costs (LCC) in the defence capability development processes. The Logistics Support Analysis (LSA) is use to evaluate the ILS activities implemented for armoured vehicles. Improper implementation would result inefficient and ineffective whereby the assets cannot be sustained which eventually lead to low level of operational readiness. Therefore, a unique MAF process needs to be developed, adapted and properly applied with the ILS principles in all phases of the development process.